Modelling Intergovernmental Fiscal Equalisation in Zimbabwe: Towards Resolving Vertical and Horizontal Fiscal Imbalances - Chakunda, Vincent; Dzingirai, Canicio; Chikerema, Arthur (Public Finance Quarterly, 2021)
The paper deploys a mixed method approach in modelling intergovernmental fiscal equalisation in Zimbabwe. The desirability of the proposed fiscal capacity model is premised on the argument that the anecdotal vertical fiscal imbalance is a structural issue whose antidote is reassignment of revenue or expenditure responsibilities among different governmental tiers. The fiscal capacity model, as we have proposed, is underpinned by five variables, namely, total amount to be allocated as declared in the national budget, poverty index (poverty prevalence rate), population of the area, size of the local economy (revenue/GDP ratio) and the estimated intrinsic value of the sub-soil natural resource endowments of the area.